Key Factors of Urban Public Transportation Services Implementation in Indonesia: A Knowledge Management Perspectives - Adhitama, Raihansyah Yoga; Giffari, Rafi; Sensuse, Dana Indra; Eitiveni, Imairi; Hidayat, Deden Sumirat; Indria, Sofi (Journal La Multiapp, 2024)
It is well-recognized that the availability of public transportation has a significant impact on urban transportation networks. In Indonesia, the government is still having difficulties to establish a reliable public transportation system. One important aspect that can be utilized in establishing a reliable public transportation system is to utilize knowledge management in its services. This study aims to identify key factors from knowledge management perspectives related to the implementation of public transportation services. To achieve this objective, this study conducted qualitative research on 12 users of public transportation services in Indonesia. The results of this study indicate that there are several key factors related to the implementation of public transportation services from knowledge management perspectives, such as Real-Time Information, Digital Accessibility, User Engagement and Trust, Platform Functionality and Quality, Digital Inclusive Strategy, Knowledge Dissemination Method, Help Desk Reliability, and Knowledgeable Officer.